Influence of Bypass Fat Supplementation on Productive Performance and Economics of Lactating Cows - Singh, Sunil; Singh, A K; Gautam, U S; Singh, Archana; Tiwari, D K; Sahay, Ratna (Indian Journal of Extension Education, 2020)
The present experiment was conducted on 20 healthy lactating cows of nearly similar age and stage of lactation to study Bypass fat supplementation on Productive Performance and Economics in lactating cattle in Unnao district. Cows were divided into 2 groups (10 cows in each group), which T1 was fed through farmers practices (control) (Use of concentrate, wheat straw and fodder) and T2 group in addition to farmers practices was supplemented with Bypass fat (20 g/day milk yield for 60 days and Fenbendazole 3 gm tablet used orally as dewormer at once). The results revealed that the milk yield and fat percent was significantly higher (P<0.05) in T2 group as compared to T1. However, the Protein and SNF percent was non-significantly but numerically higher in T2 group as compared to T1. The economics status of supplementation of bypass fat was 24 Rs/day /animal with 77.41 per cent more return over the farmer’s practices (T1). Based on the observations the bypass fat supplementation to lactating cows is beneficial in terms of increasing milk production, fat percent and higher over return.